Studi Susut Energi Pada Penyulang Perunggu Gardu Induk Sutami - Samsurizal Samsurizal; Hanif Fauji (Sekolah Tinggi Teknik - PLN, 2020)
Power shrinking events in the distribution network are unavoidable events, but the amount of power shrinking that occurs can still be overcome or suppressed to a minimum for that is the need to prevent the onsanion of large amounts of shrinking by means of maintenance and repair of distribution system equipment, the calculation of power shrink is carried out by quantitative method where the data retrieved is the peak current time data. From the results of the study conducted in The Bronze Purgator obtained a daily average shrinkage value of 5.37%, and the calculation result was obtained that the average energy shrinkage that occurred within a month was 3981,717 kWh.